Mites of the families Neopygmephoridae and Scutacaridae associated with variegated mud-loving beetles (Coleoptera: Heteroceridae) from Russia and Kazakhstan - Khaustov, Alexander A.; Sazhnev, Alexey S. (Zootaxa, 2016)
In this paper we describe a new monotypic genus Protoallopygmephorus gen. nov. and two new species of the genus Allopygmephorus Cross, 1965, A. spinisetus sp. nov. and A. punctatus sp. nov. Specimens were collected phoretic on beetles of the family Heteroceridae (Coleoptera) in Russia and Kazakhstan. Scutacarus sphaeroideus Karafiat, 1959 (Acari: Scutacaridae) is recorded on Heteroceridae for the first time.